A Arquiconfraria do Cordão de São Francisco em Minas Gerais : história, culto e arte (1760-c.1850) - Maria Clara Caldas Soares Ferreira (2019)
The purpose of this research is to understand the development of the Archconfraternity of the Cord of Saint Francis in Minas Gerais, between the years of 1760-1850, when it became known as the branch of the Franciscan worship undertaken by “colored people”. For this purpose, this study was sustained by the documentation issued by the corporation in records on the trajectory of the registrars and in the devotional articles found in the chapels. The theoretical framework conformed to the classical authors who approached subjects such as religion societies of laypersons, slavery and devotional and artistic culture. It was yet supported by academic papers on prestige and social distinction. The methodology was founded on the documental research of manuscripts, regarding the materiality of the devotional articles, and on the bibliographic research of varied artworks, books, academic papers and articles on the historical context studied. It was examined that the corporation has adopted strategies for sharing the spiritual practices and insignias that were hitherto considered by the Franciscan third brothers as exclusive of the Third Order of Penance. The “free-colored men of the Cord” demonstrated to be suitable for mediating the disputes imposed by the Franciscan third brothers, such as capable of building their own temple, with architectonic and ornamental solutions that were similar between each other, and also of establishing small religious associations in localities remote from the urban areas. In the first part of the nineteenth century, the Archconfraternity of the Cord of Saint Francis started benefiting from the prerogative of Third Order of Penance in places where the branch of the Franciscan worship reinforced by the “white men” had never built a sanctuary.